Epidemiology of gasterointestinal nematodes in migratory sheep and goats in north-west humid Himalayan region - Jithendran, K P (The Indian Journal of Animal Sciences, 2012)
A study conducted on migratory sheep and goats of Himachal Pradesh revealed 94% infection with gastrointestinal nematodes. The intensity of infection in terms of monthly mean eggs per gram of faeces (EPG) revealed in July-September with high intensity of infection with an overall EPG ranging from 236 to 3 400 in sheep and 325 to 5 908 in goats, mainly because of species of Strongyloides, Trichostrongylus, Haemonchus, Oesophagostomum, Bunostomum and Chabertia in the decreasing order of prevalence. The role of migratory sheep and goats in the spread, and seasonal outbreak of parasite induced morbidity and mortality has been discussed.